Optimizing Accounting Practices for Financial Management in Orchid Cultivation: A Comprehensive Approach for Farmers in Dadaprejo Junrejo Village, Batu City - Wuryan Andayani; Sutrisno T (Universitas Pendidikan Ganesha, 2023)
Founded in 2007, DD Orchid in Dadaprejo, Junrejo District, Batu City, is a notable player in orchid cultivation, offering a diverse range of orchids at various price points. Despite its success, the organization faces challenges such as irregular bookkeeping, disorganized stock management, and a lack of basic bookkeeping training for collaborating farmers. This empirical research investigates the impact of proposed solutions on enhancing operational efficiency. The study, spanning a 2-hectare property with advanced watering systems and involving 80-100 plasma-assisted farmers, addresses these challenges through strategic interventions. Firstly, it explores the impact of elevating human resource quality within DD Orchid. Secondly, the implementation of disciplined administrative and financial practices, including regular financial statements, is examined for its effect on overall management. Thirdly, the study evaluates the impact of optimizing orchid code management. Lastly, the research investigates the effectiveness of providing training to plasma-assisted farmers on creating simple financial reports. The anticipated results aim to provide empirical evidence on the effectiveness of these solutions in streamlining administrative, financial, bookkeeping, and human resource management within DD Orchid and among its collaborating farmers.